2012
DOI: 10.1016/j.neuroimage.2011.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional fear, negative affectivity, and neuroimaging response to visually suppressed emotional faces

Abstract: “Invisible” stimulus paradigms provide a method for investigating basic affective processing in clinical and non-clinical populations. Neuroimaging studies utilizing continuous flash suppression (CFS) have shown increased amygdala response to invisible fearful versus neutral faces. The current study used CFS in conjunction with functional MRI to test for differences in brain reactivity to visible and invisible emotional faces in relation to two distinct trait dimensions relevant to psychopathology: negative af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 82 publications
2
53
0
1
Order By: Relevance
“…Enhanced activity in this subcortical pathway has been repeatedly reported during nonconscious perception of static facial and whole-body expressions of fear and joy in blindsight patients (20,25,27) as well as in healthy subjects in whom nonconscious perception was induced by experimental manipulations such as visual masking (19,21,23), binocular rivalry (33,34), or flash suppression (35). Consistent with these data, recent anatomical studies revealed the existence of direct anatomical connections between the SC, Pulv, and Amg in nonhuman primates (36), and in vivo tractography found the same connections in healthy human subjects and in patient GY (37).…”
Section: Discussionmentioning
confidence: 83%
“…Enhanced activity in this subcortical pathway has been repeatedly reported during nonconscious perception of static facial and whole-body expressions of fear and joy in blindsight patients (20,25,27) as well as in healthy subjects in whom nonconscious perception was induced by experimental manipulations such as visual masking (19,21,23), binocular rivalry (33,34), or flash suppression (35). Consistent with these data, recent anatomical studies revealed the existence of direct anatomical connections between the SC, Pulv, and Amg in nonhuman primates (36), and in vivo tractography found the same connections in healthy human subjects and in patient GY (37).…”
Section: Discussionmentioning
confidence: 83%
“…This consid eration is particularly important given that even when behavioral correlates of semantic processing are eliminated, electrophysiological correlates may still be present (Heil, Rolke, & Pecchinenda, 2004) . Likewise, studies have reported differential amygdala activation to threatening and neutral stimuli under binocular rivalry (e.g., Pasley, Mayes, & Schultz, 2004;Vizueta et al, 2012). With both these ERP and fMRI measures it is important to consider that any pair of stimuli may induce differ ential activation at the neural level.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies employing CFS in conjunction with functional MRI (fMRI) have recorded differential amygdala re sponses to invisible fearful and neutral faces Vizueta, Patrick, Jiang, Thomas, & He, 2012). However, these studies did not report convergent changes in behavior or auto nomic physiological arousal that characterize functional threat responses.…”
mentioning
confidence: 99%
“…For CFS and related phenomena, fMRI studies have used anaglyphs (Bahrami et al, 2007;Jiang & He, 2006;Tse et al, 2005;Vizueta et al, 2012;Watanabe et al, 2011;Williams et al, 2004), the mirror stereoscope , prism stereoscopes (Schurger et al, 2010;Yuval-Greenberg & Heeger, 2013) and HMDs (Troiani & Schultz, 2013).…”
Section: Neuroimagingmentioning
confidence: 99%